Circadian activity and sleep architecture in autism spectrum disorder mouse model with Chd8 mutation - Yu, Jiahui; Deki-Arima, Norie; Saito, Yuki C.; Furutani, Naoki; Nishiyama, Masaaki; Nakayama, Keiichi I.; Niwa, Yasutaka; Hirano, Arisa; Sakurai, Takeshi (Frontiers in Sleep, 2025)
Individuals with autism spectrum disorder (ASD) frequently experience sleep disturbances, including difficulties in sleep initiation, reduced total sleep time, and excessive daytime sleepiness. Among them, those carrying mutations in the CHD8, a high-penetrance ASD risk gene, often exhibit both core ASD symptoms and pronounced sleep abnormalities. However, detailed evaluations of sleep architecture and circadian activity in this population remain limited. In this study, we characterized the daily sleep patterns of Chd8 heterozygous knockout mice of both sexes, an established ASD model, using electroencephalography (EEG)/electromyography (EMG) recordings. Chd8 knockout mice exhibited reduced wakefulness and increased rapid eye movement (REM) sleep duration during the dark phase, along with disruption of normal daily REM sleep fluctuations. Furthermore, analysis of REM latency distributions revealed a reduction in short-latency REM bouts (i.e., <150 seconds) during the light phase. Chd8 knockout also showed reduced locomotor activity at night. These findings provide new insights into the sleep phenotypes associated with CHD8-related ASD and may help elucidate the underlying neurobiological mechanisms of sleep disturbances in this condition.